Plasma biomarkers and their correlation in adult children of parents with Alzheimer’s disease - Huang, Ling-Chun; Chen, Ming-Hui; Chuu, Chih-Pin; Li, Kuan-Ying; Hour, Tzyh-Chyuan; Yang, Yuan-Han (Frontiers in Aging Neuroscience, 2022)
Family history of late onset Alzheimer’ s disease (AD) is associated with changes in several cerebrospinal fluid biomarkers in cognitively normal individuals. However, potential changes in plasma biomarkers remain unknown. This study aimed to evaluate potential plasma biomarkers and their correlation in cognitively normal adult children (AC) and to compare this data with their AD parents and unrelated normal controls (NC). Participants with dementia due to AD, their AC and NC were recruited. Plasma samples were assessed for amyloid beta (Aβ)1-42, Aβ1-40, total tau (T-tau) and phosphorylated tau (P-tau). Kruskal-Wallis test was used for the comparison of this data between the three groups. Spearman rank correlation was used for evaluation of the correlations between Aβ1-40 and Aβ1-42, and T-tau and P-tau in the AD and AC groups. A total of 99 subjects completed the assessment (30 had AD; 38 were AC group; and 31 were NC). Compared with the NC group, there were significantly higher levels of Aβ1-40, P-tau and P-tau/T-tau ratio, and lower levels of Aβ1-42 and Aβ1-42/Aβ1-40 ratio in the AD and AC groups. The correlation between the level of Aβ1-42 and Aβ1-40 and level of T-tau and P-tau was only observed in the AC but not in the AD group. AC of AD parents demonstrate some indicators of AD like their parents. Disruption to the correlation between Aβ and tau in AD may be a biomarker for the development of AD in AC, which should be examined in a longitudinal cohort.